'Aestheticization of Poverty' and 'Manufactured Consent': How Power Imbalances Between Stakeholders Led to the Failure of the Kannankund 'Model Village' Housing Rehabilitation Project. (March 2023) - Mohandas, Meghna; Purayil, Vivek Puthan
In the aftermath of the Kerala floods of 2018, a model village project was proposed in the Kannankund area of Malappuram, Kerala to rehabilitate 34 families who had lost their houses. The project was awarded to a group of technical experts who proposed housing designs that prioritized the aesthetic language of the model village (Roy, 2003). While they engaged in participatory models to establish frameworks for design, the authors of this article observe that the process of participation was largely a smokescreen exercise to 'manipulate' beneficiaries into choosing options that were reflective of the aesthetic values central to the project (Arnstein, 1969; Burawoy, 1979). By situating community participation within analytical frameworks of public participation, this article seeks to analyse how skewed power dynamics in beneficiary engagement resulted in circumvention of community needs in the Kannankund model village project. The findings of this article hold significance in informing housing and urban planning practices in projects where participatory processes are being invoked to engage with marginalized communities.